Home Based Walking Exercise For Nursing Interventions - Huwaina Af’idah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Chronic Obstructive Pulmonary Disease (COPD) is a lung condition characterized by persistent and typically progressive respiratory symptoms and airflow limitation. This disease is associated with an excessive chronic inflammatory response in the airways and lung parenchyma due to exposure to harmful gases or particles. The objective of this study is to evaluate the changes in oxygen saturation and activity tolerance in COPD patients before and after performing home-based walking exercises, pursed lips breathing, and effective coughing. The research method used a descriptive design in the form of a case report with a nursing process approach. The instruments used included assessment sheets and oximetry to measure oxygen saturation. The study subjects were patients with COPD. The results showed that before the intervention, the patient's (Mrs. E) oxygen saturation was 96%, and she reported difficulty engaging in activities due to fatigue and shortness of breath. After three days of intervention, her oxygen saturation increased to 99%, and she was able to perform outdoor activities without experiencing shortness of breath. In conclusion, home-based walking exercises, pursed lips breathing, and effective coughing can improve oxygen saturation, increase activity tolerance, and reduce dyspnea and fatigue